Early Outcomes of Three Total Arch Replacement Strategies for DeBakey Type I Aortic Dissection - Xie, Enzehua; Wu, Jinlin; Qiu, Juntao; Dai, Lu; Qiu, Jiawei; Luo, Qipeng; Jiang, Wenxiang; Cao, Fangfang; Zhao, Rui; Fan, Shuya; Gao, Wei; Guo, Hongwei; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: This study employed three surgical techniques: total arch replacement (TAR) with frozen elephant trunk (FET), aortic balloon occlusion technique (ABO) and hybrid aortic arch repair (HAR) on patients with type I aortic dissection in Fuwai Hospital, aiming to compare the early outcomes of these surgical armamentariums. Methods: From January 2016 to December 2018, an overall 633 patients (431 of TAR+FET, 122 of HAR, and 80 of ABO) with type I aortic dissection were included in the study. Thirty-day mortality, stroke, paraplegia, re-exploration for bleeding, and renal replacement therapy were compared using the matching weight method (MWM). Results: After MWM process, the baseline characteristics were comparable among three TAR groups. It showed that ABO group had the longest cardiopulmonary bypass (p < 0.001) and aortic cross-clamp time (p < 0.001), while the operation time was longest in the HAR group (p = 0.039). There was no significant difference in 30-day mortality among groups (p = 0.783). Furthermore, the incidence of stroke (p = 0.679), paraplegia (p = 0.104), re-exploration for bleeding (p = 0.313), and CRRT (p = 0.834) demonstrated no significant difference. Of note, no significant differences were found regarding these outcomes even before using MWM. Conclusions: Based on the early outcomes, the three TAR approaches were equally applicable to type I aortic dissection. We may choose the specific procedure relatively flexibly according to patient status and surgeon's expertise. Importantly, long-term investigations are warranted to determine whether above approaches remain to be of equivalent efficacy and safety.